Analisis Kemampuan Berpikir Kreatif Siswa Kelas XI IPA 3 SMAN 5 Bulukumba pada Penerapan Model Kooperatif Tipe STAD (Students Teams Achievement Divisions) dengan Mind Mapping (Studi pada Materi Pokok Larutan Asam Basa) - Satriah, Susi; Jusniar, Jusniar; Sulastry, Taty (ChemEdu, 2021)
This descriptive study aims to determine how much ability of think creative of students on every aspect of the creative thinking skills (CTS) in terms of process and product. The subjects of this study were the students of class XI IPA 3 SMAN 5 Bulukumba. The class were taught using STAD Type of Cooperative Learning model with mind mapping. The instrument used in this study was observation sheet to measure the CTS of process and achievement test to measure CTS of product. The indicators achievement of CTS on application STAD type of Cooperative Learning model and mind mapping are: (1) fluency aspect reached 64.69 % belonging to high category, (2) flexibility aspect achieved 52.50 % belonging to low category, (3) originality aspect achieved 40.00 % belonging to lower category, and (4) elaboration aspect achieved 63.44 % belonging to medium category. Whereas the indicators achievement of CTS for the manufacture of mind mapping result are: (1) fluency aspect reached 74.22 % belonging to high category, (2) flexibility aspect achieved 66.41 % belonging to high category, (3) originality aspect achieved 53.13 % belonging to low category, and (4) elaboration aspect achieved 73.44 % belonging to high category. The Data were obtained by providing achievement test to measures the CTS of students during the learning process takes place. Values of achievement test were analysed using descriptive statistical analysis and is obtained the indicators of achievement for each aspect of that is to aspects of fluency reached 98.1% belonging to very high category, flexibility aspects achieved 91.5% belonging to very high category, and elaboration aspect reached 58.6% belonging to medium category. It was concluded that the aspects of fluency is an indicator that reach the highest percentage from other aspects of indicator of the creative thinking skills.